2011
DOI: 10.1021/jp205561h
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Jet Discharge Matrix Isolation and Computational Study of Bromine Atom Complexes: Br···BrXCH2 (X = H, Cl, Br)

Abstract: Halogen atoms are important reactive radicals in the atmosphere. In this work, pulsed jet discharge matrix isolation spectroscopy and computational methods were used to characterize prereactive complexes of halogen atoms with simple halons. Our experiments combined matrix isolation techniques with a pulsed DC discharge nozzle, where a dilute CH(2)XBr (X = H, Cl, Br)/rare gas sample was gently discharged and the products were deposited onto a cold KBr window. The Br···BrCH(2)X (X = H, Cl, Br) complexes were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 72 publications
2
6
1
Order By: Relevance
“…Reid et al have argued, on the basis of computational studies, that an ion-pair (RCBr 2 + ···Br − ) resonance structure is a significant contributor for 9 in the condensed phase and that Hbonding solvents such as water should help stabilize this species. 27 This is certainly consistent with our observations of significant products formed via 9 when water and other Hbonding species (see below) are added. Adding water to the Scheme 1.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…Reid et al have argued, on the basis of computational studies, that an ion-pair (RCBr 2 + ···Br − ) resonance structure is a significant contributor for 9 in the condensed phase and that Hbonding solvents such as water should help stabilize this species. 27 This is certainly consistent with our observations of significant products formed via 9 when water and other Hbonding species (see below) are added. Adding water to the Scheme 1.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…The effects of an explicit toluene solvent molecule on photodegradation reaction of BDE209 are investigated by using the density functional theory (DFT) , and time-dependent density functional theory (TD-DFT). The M06 functional combined with the TD method is employed, which has been proven successful in describing the noncovalent interactions and the excitation properties of certain organic compounds. The hybrid basis set denoted as 6-311+G(d)-LANLdp is used for all calculations. For bromine, the LANL2DZ basis set is used and is augmented with polarization functions of d symmetry and diffuse functions of p symmetry .…”
Section: Methodsmentioning
confidence: 99%
“…These issues can be resolved by using DFT with effective core potentials. Previous studies have shown that reliable geometries, energies, and frequencies can be obtained when effective core potentials are used in tandem with density functional theory (DFT). Effective core potentials were only available for the heavier halides iodine and bromine, whereas for chlorine and fluorine no effective core potential was available (or needed) and thus the full electron representation was used in the computations. We employed the Minnesota functional M11 .…”
Section: Theorymentioning
confidence: 99%